A novel and practical asymmetric synthesis of dapoxetine hydrochloride - Zhu, Yijun; Liu, Zhenren; Li, Hongyan; Ye, Deyong; Zhou, Weicheng (Beilstein Journal of Organic Chemistry, 2015)
A novel and practical asymmetric synthesis of dapoxetine hydrochloride by using the chiral auxiliary (S)-tert-butanesulfinamide was explored. The synthesis was concise, mild, and easy to perform. The overall yield and stereoselectivity were excellent.
Keywords: asymmetric synthesis; dapoxetine hydrochloride; stereoselectivity; (S)-tert-butanesulfinamide

(untitled) - Althof, S. E. (J. Urol., 2006)

(untitled) - Zhou, C.; Jiang, X.; Xu, Z.; Guo, L.; Wang, H.; Zhang, D.; Shi, B. (J. Sex. Med., 2010)

(untitled) - Sorbera, L. A.; Castaner, J.; Castaner, R. M. (Drugs Future, 2004)

(untitled) - Darcsi, A.; Tóth, G.; Kökösi, J.; Béni, S. (J. Pharm. Biomed. Anal., 2014)

(untitled) - Torre, O.; Gotor-Fernández, V.; Gotor, V. (Tetrahedron: Asymmetry, 2006)

(untitled) - Siddiqui, S. A.; Srinivasan, K. V. (Tetrahedron: Asymmetry, 2007)

(untitled) - Chincholkar, P. M.; Kale, A. S.; Gumaste, V. K.; Deshmukh, A. R. A. S. (Tetrahedron, 2009)

(untitled) - Kang, S.; Lee, H.-K. (J. Org. Chem., 2010)

(untitled) - Kim, S. J.; Jeon, T. H.; Min, I. S.; Kim, I. S.; Jung, Y. H. (Tetrahedron Lett., 2012)

(untitled) - Khatik, G. L.; Sharma, R.; Kumar, V.; Chouhan, M.; Nair, V. A. (Tetrahedron Lett., 2013)

(untitled) - Cogan, D. A.; Liu, G.; Kim, K.; Backes, B. J.; Ellman, J. A. (J. Am. Chem. Soc., 1998)

(untitled) - Robak, M. T.; Herbage, M. A.; Ellman, J. A. (Chem. Rev., 2010)

(untitled) - Arava, V. R.; Gorentla, L.; Dubey, P. K. (Beilstein J. Org. Chem., 2012)

(untitled) - Borg, G.; Cogan, D. A.; Ellman, J. A. (Tetrahedron Lett., 1999)

WO Pat. Appl. - Dave, A. M.; Patel, D. J.; Kumar, R.; Dwivedi, S. D. (A process for preparing (+)-dapoxetine and its salts, 2007)